Strategi Pengelolaan UMKM dalam Mempertahankan Usaha Pasca Bencana Kebakaran Ditinjau Berdasarkan Perspektif Islam - Sadiyah, Neni; Juhadi, Juhadi; Apriana, Agung (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In economic activities there are various kinds of businesses carried out by people to fulfill their economy. One of them is trading, trading can be done anywhere but mostly it is done in a place which is usually called a market. Especially in the Pagaden area, it is no stranger to the name market. The market is a place that is a source of income for the community, especially in the Pagaden area. However, what happens if the community's place to fulfill their economy experiences an unexpected event, namely a fire, they have to restart their destroyed business. Therefore, this research was conducted to contains traders' strategies for maintaining their business after a market fire occurred at Pagaden Market, Subang Regency. The type of research used is qualitative, using interview research methods with participants, namely MSMEs and SDI actors in it. The results of this research show that traders maintain their business. implementing a marketing management strategy in the form of selling a variety of products. Apart from that, if viewed from an Islamic economic perspective, the marketing management strategy in Islam is being honest with the product, being fair in setting prices. The risk management strategy is in accordance with the Islamic economic perspective by not allowing any means to be justified. to get more profits and carry out better business planning.